2017
DOI: 10.12776/ams.v23i1.816
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salt Bath Nitriding on Surface Roughness Behaviour of Aisi 4140 Steel

Abstract: In the present research, AISI 4140 steel was nitrided in salt bath to study and analyze the behaviour of the surface roughness. The structural surface characterization behaviour of the nitrided steel was compared to the behaviour of the same steel which was untreated. The nitriding process was implemented in the salt bath component at ten different times (from 1 h to 10 h) when the temperature was constant at (580ºC). The influence of nitriding treatment on structural properties of the material was studied by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
1
0
1
Order By: Relevance
“…The salt bath nitriding process improved the surface characteristics of AISI 4140 steel. It was found that enhancing the nitriding time significantly raises the Ra, Rq, and Rz [15]. During plasma nitriding, various parameters of the surface roughness of 30CrMoV9 steel was evaluated.…”
Section: Researchmentioning
confidence: 99%
“…The salt bath nitriding process improved the surface characteristics of AISI 4140 steel. It was found that enhancing the nitriding time significantly raises the Ra, Rq, and Rz [15]. During plasma nitriding, various parameters of the surface roughness of 30CrMoV9 steel was evaluated.…”
Section: Researchmentioning
confidence: 99%
“…Veličina pora povećava se pri višim temperaturama, a nastaju kao rezultat akumulacije intersticijski rastvorenih atoma azota na preferencijalnim mestima, kao što su granice zrna, da bi se formirao molekularni azot [37]. Ghelloudj je sa saradnicima [38] pokazao da nitridi ε-Fe 2-3 (N,C) i γ'-Fe 4 (N,C) prisutni u sloju jedinjenja AISI 4140 povećavaju mikrotvrdoću (406-502 HV 0.3 ), a početne vrednosti hrapavosti površine nitriranih uzoraka su bile veće od uzoraka bez nitriranja. U literaturi [39] eksperimentalno je pokazano da povećanje parametara nitriranja u sonom kupatilu (vreme tretmana i temperatura) povećava tvrdoću površine i tvrdoću profila AISI 1045.…”
Section: Područje Primeneunclassified